ELECTRONIC, STRUCTURAL AND PHARMACOCINETIC CHARACTERIZATION OF TRICYCLIC ALKALOID ALTERNAMIDE A: A SEMI-EMPIRICAL QUANTUM STUDY AND ADMET - Estácio Sandy Pereira; Da Silva Mendes, Francisco Rogênio; Marinho, Emanuelle Machado; Campos, Othon Souto; Marinho, Márcia Machado; Marinho, Emmanuel Silva (International Journal of Research -GRANTHAALAYAH, 2019)
Chagas disease is one of the biggest socioeconomic problems in Latin America. Caused by the protozoan parasite Trypanosoma cruzi, affecting 7 million people, causing approximately 14,000 deaths per year. Alternamide, a tricyclic alkaloid present in Alternanthera littoralis, an herbaceous plant found on beaches of the Brazilian its extracts are used in traditional medicine for treatment of infectious and inflammatory diseases, which showed anti Trypanocida activity. In this context, in the present work we present the results of the electronic, structural and pharmacokinetic characterization study of the promising phytopharmaceutical Alternamide A. Using the semi-empirical quantum formalism it was possible to identify the most stable conformation, boundary orbitals, calculate to identify nucleophilic sites and reactivity descriptors. Through in silico absorption, distribution, metabolism, excretion and toxicity (ADMET) simulations, including solubility, blood-brain barrier (BHE), plasma protein binding, CYP2D6 binding, gastrointestinal absorption and hepatotoxicity, it was observed that good oral bioavailability and high-water solubility high gastrointestinal absorption. The synthetic accessibility score was 2.75, which means that it would be easy to synthesize the molecule under study. Highlighting what this study represents is a key step for future molecular docking and drug design studies for the development of inhibitors of the evolutionary forms of the molecule T-crossed.